Design and experiment of a subsoiling variable rate fertilization machine - Qi, Jiangtao; Tian, Xinliang; Li, Yang; Fan, Xuhui; Yuan, Hongfang; Zhao, Jiale; Jia, Honglei (International Journal of Agricultural and Biological Engineering, 2020)
In order to improve soil fertility and fertilizer utilization, a subsoiling variable rate fertilization machine based on conservation tillage and precision agriculture was designed and tested. The relationship between suspension parameters and penetrating distance was analyzed, and a matching model between fertilizing quantity and penetrating distance was established. The variable-rate fertilization control machine was developed based on an Advantech PCM-9363 industrial control mainboard. The machine operates under two patterns: DGPS-based positioning and straight-line path positioning based on a planar coordinate system. This machine can perform on-demand fertilization according to the spatial differences in soil nutrients and the prescription maps pre-set before the operation. Field experiments showed the machine has a subsoiling stability of 92.5%, a soil breaking rate of 61.1%, a maximum positioning relative error of 2.68% and a maximum variable rate fertilization error of 3.89%. The subsoiling performance and variable rate fertilization indices of this machine satisfy the requirements of GB/T24675.2-2009. The tested indices meet the national and industrial standards and satisfy the design requirements. The findings of the research can be used as the structural design of the subsoiling variable rate fertilization machine.Keywords: agricultural machinery, conservation tillage, precision agriculture, subsoiling; variable rate fertilizationDOI: 10.25165/j.ijabe.20201304.5757Citation: Qi J T, Tian X L, Li Y, Fan X H, Yuan H F, Zhao J L, et al. Design and experiment of a subsoiling variable rate fertilization machine. Int J Agric & Biol Eng, 2020; 13(4): 118–124.